STRUCTURAL ENVIRONMENTS AROUND MOLYBDENUM IN SILICATE GLASSES AND MELTS. II. EFFECT OF TEMPERATURE, PRESSURE, H2O, HALOGENS AND SULFUR - Farges F.; Siewert R.; Ponader C.W.; Brown G.E.; Pichavant M.; Behrens H. (My University, 2006)
The local structure around molybdenum (at a concentration of 2000 ppm) in densified silicate glasses (to 7 kbar), melts (to 1210 K), and fluid-bearing (either H2O, halogens, or sulfur) glasses was investigated by the means of X-ray absorption fine structure (XAFS) spectroscopy at the molybdenum K-edge. The spectra show that molybdate moieties [i.e., Mo(VI)O42-] are the dominant form of molybdenum in anhydrous melts and in densified glasses, with only a minor amount of tetravalent molybdenum. Also, H2O and halogens have a limited effect on the local structure of molybdenum by promoting tetravalent coordination, but they do not complex Mo. In contrast, sulfur is found to complex molybdenum at moderate oxygen and sulfur fugacities. Thio-oxo-molybdate moieties [Mo(IV,V,VI)OnSn (n = 1, 2, 3)] are observed in sulfur-bearing glasses. Thio-oxo-molybdate moieties are characterized by Mo=S2- bonds, which result in these moieties being disconnected (mobile) within the melt. These moieties also polymerize with decreasing redox state of Mo (as Mo-S units), enhancing molybdenite saturation and nucleation in the melt. A new and largely unexplored area of research involving the structure and stability of thio-molybdate moieties in magmatic systems is outlined, which can help reconcile some of the apparent discrepancies in the geochemistry of molybdenum in synthetic systems versus natural systems, in particular in systems where molybdenum partitions into the fluid phase.
Keywords: FLUIDS; GLASSES AND MELTS; MOLYBDENUM; SULFUR; XAFS SPECTROSCOPY